Electrochemical immunosensor using nanotriplex of graphene quantum dots, Fe3O4, and Ag nanoparticles for tuberculosis. (10th November 2018) - Tufa, Lemma Teshome; Oh, Sangjin; Tran, Van Tan; Kim, Jeonghyo; Jeong, Ki-Jae; Park, Tae Jung; Kim, Hwa-Jung; Lee, Jaebeom
Abstract: A glassy carbon electrode (GCE) is modified with a nanotriplex [ i.e., three nanolayers consisting of graphene quantum dot (GQD)-coated Fe3 O4 @Ag core-shell nanostructure (Fe3 O4 @Ag/GQD)]. The nanotriplex is a sensitive electrochemical biosensor platform for detecting Mycobacterium tuberculosis antigen (culture filtrate protein; CFP-10). Gold nanoparticles (AuNPs) conjugated to an anti-CFP-10 antibody are used as a label for signal amplification. The nanotriplex-based sensing platform attains synergetic electrochemical performance by the three different roles of three nanomaterials: Fe3 O4 increases the surface to volume ratio; Ag enhances electrical conductivity; and GQD for loading more of the anti-CFP-10 antibody onto the electrode. The electron transfer kinetics at the surface of the electrode is simulated by means of the Butler–Volmer model. A sandwich-type immunoassay results by immobilizing the first antibody on the Fe3 O4 @Ag/GQD-modified GCE and by incubating this system with the antigen and then with AuNPs conjugated with the second anti-CFP-10 antibody (Ab2 −AuNPs). The AuNPs are quantified by exposing the immunocomplex to a potential of 1.3 V for 40 s and scanning by differential pulse voltammetry. The immunosensor shows a wide linear range (0.005–500 μg/mL) with a limit of detection (signal/noise = 3) reaching 0.33 ng/mL. The results suggest that the reliable and robust performance with high selectivity and simple operation may be extended to detection of other biomarkers of pathogenic bacteria. Highlights: The nanotriplex particles (Fe3 O4 @Ag/GQD) were prepared with different reagents by stepwise functionalization. An electrochemical biosensor was developed for detection of a Mtb antigen CFP-10 using a GCE modified with a nanotriplex. The nanotriplex-based sensing platform showed synergetic electrochemical performance by means of three nanomaterials. The immunosensor showed high selectivity and a wide linear range with a LOD (S/N = 3) reaching 0.33 ng/mL.